Penerapan Atraumatic Care dengan Kecemasan Anak Pra-Sekolah Saat Proses Hospitalisasi - Hotmaria Julia Dolok Saribu; Wasis Pujiati; Endang Abdullah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Hospitalization is a crisis condition in children when the child is sick and hospitalized. Getting sick and being hospitalized is an unpleasant experience and most of the nursing process makes children afraid and even traumatized. Atraumatic care is a therapeutic care service in the setting of children's health services through the use of actions that reduce physical and psychological distress experienced by children and parents. The application of atraumatic care with audiovisual, namely providing cartoon videos, this therapy is very effective in reducing anxiety in children who are hospitalized. The goal is to reduce the anxiety due to hospitalization with Atraumatic care. Method The research method is a quasi-experimental design with a pre and post-test control group. Analysis of the data using the Wilcoxon test and to test the differences between the two groups using the independent test or Mann Whitney test. A sample of 56 preschoolers. Results: There was a difference between preschool children's anxiety during hospitalization in the experimental group and the control group (p-value 0.001). The conclusion is that there is an effect of applying audio-visual atraumatic on the anxiety of preschool children. Suggestions should apply audio-visual atraumatic care to reduce anxiety in pre-school children